Los venenos de cacería en la amazonia colombiana: ¿sustancias letales o fuente de vitalidad? (2009)
ABSTRACT: Indigenous people from Colombian Amazonia and Orinoco use more than 54 species, to prepare curares with which they poison the arrows they throw. The preparation and use of this poison has a series of prescriptions and ritual prohibitions which show the connection with female body secretions, especially menstruation. Poison is regarded as any other sour, hot and putrefactive substances which originate disease and death. The contradictory feature of poisons, which causes animal death and represents a source of food and life for human beings, poses intellectual issues which indigenouspeople solve through myths originated in these toxic substances.